Frequency of fimbriation of nontypable Haemophilus influenzae and its ability to adhere to chinchilla and human respiratory epithelium. - Bakaletz, L O (1988)
To date, we have examined nearly 60 clinical isolates of nontypable Haemophilus influenzae (26 nasopharyngeal, 33 from middle ear effusions) and have found that 100% were fimbriated. The percentage of cells bearing fimbriae within each isolate varied from less than 10 to 100%, with fimbriae being either peritrichous or bipolar in distribution. Fimbriae were approximately 2.4 to 3.6 nm in width; however, there was a high degree of variability in both length and number of fimbriae per individual bacterial cell among these isolates. All isolates tested adhered to both human oropharyngeal cells and chinchilla tracheal epithelium regardless of the degree to which the particular isolate was fimbriate. The level or degree of fimbriation did not correlate with either site of isolation, biotype, strength of hemagglutination reaction, or type of effusion present in the ear. These appendages appear to be quite different from those described for type b H. influenzae in which the ability to adhere and strength of ability to hemagglutinate correlated strongly with degree of fimbriation.